The use of coal gangue as a planting substrate in arid mining areas - Yuanbo Lu; Chunwu Song; Cheng Yan; Zhengzhong Jin; Yajuan Li; Chengyun Lai; Danhua Wang (Global Ecology and Conservation)
Coal gangue, which is the primary solid waste generated during coal production and washing processes, poses significant risks to the ecological environment and social safety. This study investigated the effective use of this material as a novel component in planting substrates to improve the physicochemical characteristics of arid sandstone soil in mining areas. The goal was to use this modified substrate for the restoration of vegetation, which at the same time would allow an effective utilization of coal gangue and its removal from mining areas. Using an L16 (4^3) orthogonal experimental design, systematically investigated the effects of three factors, i.e., coal gangue, a water-retaining agent, and bentonite, applied at various levels on soil nutrient characteristics and plant growth indicators in order to optimize the formula for the planting substrate. The addition of 1500 g of coal gangue significantly increased the contents of organic matter, total nitrogen, total phosphorus, total potassium, available nitrogen, and available potassium in the substrate (p < 0.05). This enhancement promoted the growth of Kochia prostrata. With the addition of 0.4 % water-retaining agent, the available nitrogen content in the substrate increased significantly (p < 0.05). However, conditions were more favorable for seed germination and plant survival when this agent was not added. Moreover, the addition of 4 % bentonite resulted in a significant increase in the height of Kochia prostrata (p < 0.05). The comprehensive analysis using the orthogonal experimental model indicated that the optimal coal gangue to sandstone soil ratio for vegetation growth was 375:1125 g, with the water-retaining agent and bentonite added at mass fractions of 0.1 % and 2 %, respectively. This ratio significantly enhanced the nutritional composition of the planting substrate, promoting the germination and growth of Kochia prostrata. These findings provide a scientific basis for vegetation restoration in arid sandstone substrates in mining areas.